Unaccompanied mechanosensory domain mediates low expression of glycoprotein Ibα: implications for Bernard‐Soulier syndrome. (22nd December 2019) - Tao, Yue; Gan, Chi; Zhang, Xiaoqin; Liu, Lanbo; Zakas, Philip M.; Doering, Christopher B.; Mo, Xi; Li, Renhao
Abstract: Background: Disruption of protein folding or inter‐subunit interactions in the platelet glycoprotein (GP)Ib‐IX complex leads to its abnormally low expression in the plasma membrane, the hallmark of Bernard‐Soulier syndrome (BSS). Objective: To discover the molecular mechanism by which GPIbα in the absence of GPIbβ and GPIX subunits is targeted for rapid degradation. Method: The expression of GPIbα mutants with deletion or replacement of various domains were measured in transiently transfected Chinese hamster ovary cells. Results: We report evidence to suggest that induction of the unfolded protein response by the unaccompanied mechanosensory domain (MSD) is a major factor for intracellular degradation and low expression of GPIbα. Removal of the MSD produced the first GPIbα variant that, even in the absence of GPIbβ and GPIX, expressed at a level comparable to that of wild‐type GPIbα in the GPIb‐IX complex, while retaining its native ligand‐binding activity. Conclusion: Our finding has important implications on the molecular pathogenesis of BSS and the function of the GPIb‐IX complex.